Clinical and radiographic evaluation of double pelvic osteotomy to treat canine hip dysplasia - Lopes,Leandro Santos (2018)
ABSTRACT: The purpose of this study was to describe our initial experience with double pelvic osteotomy (DPO) in young dogs affected by hip dysplasia (HD) and to report their postoperative outcome. Seven dogs (four females and three males) were included in our study with mean age 8.3 (±1.7) months, and mean body weight 29.5 (±7.4)Kg. Breeds involved were: Rottweiler (n = 1), Labrador Retriever (n = 3), Golden Retriever (n = 1), Great Dane (n=1) and São Miguel Cattle Dog (n = 1). The most common history complaints were: pelvic limb lameness and pain at hip extension and hip abduction. All surgical procedures consisted of osteotomy of the ilium and pubis, acetabular ventroversion and iliac stabilization with a customized bone plate with seven screws, four screws placed at the cranial fragment and the remaining three in the caudal aspect. Average surgical time was 65.8 (±10.4) minutes and median follow-up assessment was 68 (±15) days. Fracture healing was observed within mean period of 26.3 (±8.9) days. Six patients (86%) had satisfactory outcome and one patient didn’t improve after surgery and had to undergo a total hip replacement. Our results showed that DPO is an effective treatment for HD due to the preservation of pelvic geometry and low postoperative morbidity. Since it is a recent technique, further studies are recommended.